A trypanosome-derived immunotherapeutics platform elicits potent high-affinity antibodies, negating the effects of the synthetic opioid fentanyl - Gianna Triller; Evi P. Vlachou; Hamidreza Hashemi; Monique van Straaten; Johan P. Zeelen; Yosip Kelemen; Carly Baehr; Cheryl L. Marker; Sandra Ruf; Anna Svirina; Monica Chandra; Katharina Urban; et al. (Cell Reports, 2023)
Summary: Poorly immunogenic small molecules pose challenges for the production of clinically efficacious vaccines and antibodies. To address this, we generate an immunization platform derived from the immunogenic surface coat of the African trypanosome. Through sortase-based conjugation of the target molecules to the variant surface glycoprotein (VSG) of the trypanosome surface coat, we develop VSG-immunogen array by sortase tagging (VAST). VAST elicits antigen-specific memory B cells and antibodies in a murine model after deploying the poorly immunogenic molecule fentanyl as a proof of concept. We also develop a single-cell RNA sequencing (RNA-seq)-based computational method that synergizes with VAST to specifically identify memory B cell-encoded antibodies. All computationally selected antibodies bind to fentanyl with picomolar affinity. Moreover, these antibodies protect mice from fentanyl effects after passive immunization, demonstrating the ability of these two coupled technologies to elicit therapeutic antibodies to challenging immunogens.